2017
DOI: 10.1136/vr.103778
|View full text |Cite
|
Sign up to set email alerts
|

Injection‐site lesion prevalence and potential risk factors in UK beef cattle

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…Poor vaccination compliance has been noted before in the farming community; beef farmers showed similar variability in knowledge of site of application, when asked about cattle vaccination. 28 It was interesting to note that sheep farmers appeared to know more about vaccination compared with beef farmers, despite having fewer discussions with their vet. It was encouraging to hear some respondents were excluding sick or weakly animals, which resembles indings in cattle vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Poor vaccination compliance has been noted before in the farming community; beef farmers showed similar variability in knowledge of site of application, when asked about cattle vaccination. 28 It was interesting to note that sheep farmers appeared to know more about vaccination compared with beef farmers, despite having fewer discussions with their vet. It was encouraging to hear some respondents were excluding sick or weakly animals, which resembles indings in cattle vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A more practical measure to avoid sciatic nerve damage would be to alter injection practices. The neck is the recommended site for intramuscular injection in cattle 19 but the results indicated that this site was currently not most commonly used by the participants of this study. In a US study veterinary surgeons favoured the neck for injecting reproductive products however, dairy farmers in the same study used the dorsal gluteal region more frequently 20 .…”
Section: Discussionmentioning
confidence: 93%
“…This is thought to be due to the fact that there are numerous small muscles in the neck and the likelihood that injections will fall between fascial planes is greater, allowing more rapid dispersal of drugs 11 . A UK study of beef cattle showed that ISLs can be significantly large (≤23 cm) 12 and therefore have the potential to affect the sciatic nerve's normal function.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, publications of slaughterhoused based initiatives only occasionally seek to characterize any potential bias. Mostly there is either a reliance on a sampling methodology that is structured to be representative [e.g., (46,47)], or a brief mention that a potential for bias does, or doesn't, exist [e.g., (48)], with limited attempts for more in depth assessments, such as that in (49) or the more comprehensive investigation of active sheep TSE surveillance (19). If animal health surveillance is to develop, then these types of assessments are important foundations that need to be laid, regularly evaluated and easily available to users of the data.…”
Section: Discussionmentioning
confidence: 99%